INSTALLATION FOR LARGE SIZE STAMP HARDENING TRANINIG BY WATER-AIR MIXTURE - L. A. Glazkov; M. S. Zheludkevitcsh; D. L. Zhilyanin; A. A. Tabulin; V. V. Tarbaev (Наука и техника)
The BNTU has developed a technological process for large-size stamp hardening by means of a water-air mixture.  The  basic  requirements  imposed on an hardening  installation using  a  water-air mixture are the following: provision of smooth cooling of a part in order to achieve the required  hardness and structure; possibility of machining parts of various sizes; change of modes for machining parts of various grades of steel according to any hardness rate.The peculiar features of the given installation are: a presence of microprocessor control of water-air mixture supply, possibility of simultaneous machining of a stamp set (2 parts) and position change of parts to be hardened in the process of thermal treatment.Installation for large-sized stamp hardening has been manufactured and introduced at theMinskplant of special tools and machining attachments.